Peripheral DNA methylation, cognitive decline and brain ageing: Pilot findings from the Whitehall II Imaging Study - Chouliaras, L; Pishva, E; Haapakoski, R; Zsoldos, E; Mahmood, A; Filippini, N; Burrage, J; Mill, J; Kivimäki, M; Lunnon, K; Ebmeier, K (Future Medicine, 2018)
Background DNA methylation (DNAm) has been linked with the pathophysiology of brain aging, cognitive impairment and dementia. Methods The present study investigated the association between blood genome-wide DNAm profiles, cognitive dysfunction and brain magnetic resonance imaging (MRI) measures in 48 participants of the Whitehall II imaging sub-study. Results We identified eight differentially methylated regions (DMRs) associated with cognitive impairment. Accelerated aging based on the Hannum epigenetic clock was associated with mean diffusivity and global fractional anisotropy. We also identified modules of co-methylated loci associated with white matter hyperintensities. These co-methylation modules were enriched among pathways relevant to beta-amyloid processing and glutamatergic signalling Conclusion Our data support the notion that blood DNAm changes may have utility as a biomarker for cognitive dysfunction and brain aging.